Daya Terima dan Kandungan Serat, Protein, Daya Antioksidan Keciput Kulit Buah Naga Merah dengan Penambahan Tepung Beras Merah Sebagai Jajanan Sehat - Apriliani Dwi Cahyanti; Lilik Sofiatus Solikhah; Nurdiana Nurdiana (Jurnal Siti Rufaidah, 2024)
Red dragon fruit peel has high antioxidant content and abundant availability in Indonesia but is still rarely utilized. Brown rice has a higher fiber content than white rice. Brown rice and dragon fruit skin can be processed into keciput snacks. Keciput is a snack made from glutinous rice flour wrapped in sesame seeds that can be varied in shape, color and taste. The aim is to determine the effect of the acceptability of red dragon fruit peel keciput with the addition of brown rice flour as a healthy snack. Completely randomized design (CRD) experiment with 3 treatments on red dragon fruit peel and brown rice F1 (50%:50%), F2 (60%:40%) and F3 (70%:30%). Acceptability test on 30 untrained panelists and analyzed using Kruskal Wallis and Mann Whitney tests with a significance of p<0.05. Analysis of fiber content, protein, and antioxidant power was done twice on the selected formulations. There was an effect on the acceptability of red dragon fruit skin snails and brown rice flour (p<0.001). There was no effect of acceptability in the comparison of F2 and F3 on color, aroma, and taste (p=0.252; p=8.24; p=0.247). The highest mean value of acceptability was in F2 (selected). F2 contained 27.653% fiber, 17.346% protein, and 107.268 ppm antioxidant power.